Romania : Third Review Under the Stand-By Arrangement and Request for Waiver of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2003)
This paper assesses Romania's Third Review Under the Stand-By Arrangement and a Request for Waiver of Performance Criterion. Romania's macroeconomic performance continued to be favorable, but slippages in wage policy and privatization delayed the completion of the third review. Robust GDP growth continued throughout 2002, and progress in reducing inflation and the current account deficit was better than targeted. However, financial discipline in the state-owned sector remained weak, and the end-September performance criterion on the wage bill in monitored state-owned enterprises was not observed.